Rozwiązane

7(x²-3x-2)-3(x²-6x=1) dla x=-0,2
x(3xy-y)-y(x²-xy+x) dla x=-1 y=⅕

Proszę o rozwiązanie, z góry dzięki.



Odpowiedź :

7(x²-3x-2)-3(x²-6x=1) dla x=-0,2
7([-0,2]²-3[-0,2]-2)-3([-0,2]²-6[-0,2]-1 = 8,8


x(3xy-y)-y(x²-xy+x) dla x=-1 y=⅕
[-1](3[-1]*[⅕]-[⅕])-[⅕]([-1]²-[-1]*[⅕]+[-1]) = 0,76
7((-0,2)²-3*(-0,2)-2)-3((-0,2)²-6*(-0,2)+1) = 7(0,04+0,6-2)-3(0,04+1,2+1) = 7*(-1,36)-3*2,24 = -9,52-6,72 = -16,24


(-1)*(38*(-1)*⅕-⅕)-⅕((-1)²-(-1)*⅕-1) = (-1)*(-7,6-0,2)-⅕*⅕ = (-1)*(-7,8)-1/25 = 7,8-0,04=7,76

Inne Pytanie